2012
DOI: 10.1002/wsb.135
|View full text |Cite
|
Sign up to set email alerts
|

Raptor community composition in the Texas Southern High Plains lesser prairie‐chicken range

Abstract: Predation can be a factor in preventing prey population growth and sustainability when prey populations are small and fragmented, and when predator density is unrelated to the density of the single prey species. We conducted monthly raptor surveys from February 2007 to May 2009 in adjacent areas of the Texas Southern High Plains (USA) that do and do not support lesser prairie‐chickens (Tympanuchus pallidicinctus), a candidate for protection under the Endangered Species Act. During the summer period correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 19 publications
1
16
2
Order By: Relevance
“…Previous studies have suggested survival during the breeding season is driven by vulnerability of predation due to prairiechickens being exposed on leks and distracted by courtship displays (Hartzler 1974, Schroeder and Baydack 2001, Wolfe et al 2007); most of these mortalities would be expected to be caused by sight-hunting predators such as raptors, especially when large numbers are migrating through the study area. Raptor migration on the study area occurred in late Marchearly April (Behney et al 2011(Behney et al , 2012a, which is when we documented high survival rates for both sexes. Although predation attempts were noted, Behney et al (2011) found no evidence of successful predation of lesser prairie-chickens by raptors or mammals on leks in the study area.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Previous studies have suggested survival during the breeding season is driven by vulnerability of predation due to prairiechickens being exposed on leks and distracted by courtship displays (Hartzler 1974, Schroeder and Baydack 2001, Wolfe et al 2007); most of these mortalities would be expected to be caused by sight-hunting predators such as raptors, especially when large numbers are migrating through the study area. Raptor migration on the study area occurred in late Marchearly April (Behney et al 2011(Behney et al , 2012a, which is when we documented high survival rates for both sexes. Although predation attempts were noted, Behney et al (2011) found no evidence of successful predation of lesser prairie-chickens by raptors or mammals on leks in the study area.…”
Section: Discussioncontrasting
confidence: 97%
“…We classified the mortality as an avian predation if the carcass was decapitated, showed signs of feather plucking (particularly on the breast muscle), showed single crimps on the antenna, showed beak marks on the transmitter, and/or if whitewash diagnostic of a raptor (Rezendes ) was present around the recovery site. Red‐tailed hawk ( Buteo jamaicensis ), Swainson's hawk ( B. swainsoni ), ferruginous hawk ( B. regalis ), northern harrier ( Circus cyaneus ), prairie falcon ( Falco mexicanus ), peregrine falcon ( F. peregrinus ), and great horned owl ( Bubo virginianus ) are potential avian predators in the area during the breeding season (Behney et al ). We classified the event as an unknown predator if there was enough evidence remaining at the site to attribute the mortality event to predation, but not enough to classify the event as avian or mammalian (e.g., a combination of mammal and avian evidence left at the site).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This correlation may reflect the quality of the habitat surrounding wells, or the ease of foraging in a landscape with more perch sites. Presence and higher abundance of raptors have been associated with increased number of perch sites (Behney et al 2012). Our results were similar to those of Zelenak and Rotella (1997), who found Ferruginous Hawks nesting in habitats altered by humans produced more young, potentially as a result of increased prey of Richardson's ground squirrels (Urocitellus richardsonii).…”
Section: Discussionsupporting
confidence: 89%
“…High quail mortality in the winter was consistent with the cumulative densities of Red‐tailed Hawk and Northern Harrier at that time of the year and was higher compared to the breeding season. Several species of raptors winter in the Southern Great Plains (Behney, Boal, Whitlaw, & Lucia, , ). For example, Northern Harrier does not breed in any of our study sites but arrives as early as July and leaves late in spring.…”
Section: Discussionmentioning
confidence: 99%